The role of the Malaysian Government and takaful companies in takaful protection related to women with gynaecology and mental health - Tajul Urus, Nur Sarah; Burhanuddin, Iswandi Harahap; Md. Noor, Mohamad Lukman Al Hakim; Md. Aziz, Mu’azah; Salleh, Mohd. Muslim (Knowledge Words Publications, 2024)
The notion of family takaful is a takaful scheme that offers protection and long-term savings to its members. Takaful products that have not yet been offered are in the field of gynaecology, which is concerned with the health of women from adolescence to menopause in all aspects of health, particularly those involving the functional system of the reproductive organs, for them to reach their full potential in terms of physical health, mental health, sexuality, and sociality. This subject also covers medical care during and after childbirth. Gynaecology is the discipline of diagnosing and treating women's reproductive systems, including the vagina, uterus, ovaries, and breasts. The purpose of this study is to learn about the role of the Malaysian government and Takaful companies in Takaful protection for women with gynaecology and mental health. This study used a qualitative research design, analysing the content of interviews and focus group talks with government departments and the takaful business, chosen based on the criteria of why products for this ailment have not yet been supplied to contributors. The interviews' content was analysed by categorising topics and categories as a research instrument for data collecting. The predicted results are to identify critical elements that influence the utilisation of new gynaecological and mental health goods that the takaful business can provide to women. This study will offer techniques for increasing the use of takaful products. While the suggested research is important and beneficial in understanding the elements that drive adoption, it can also help the takaful business improve its product offerings, pricing strategies, and marketing campaigns to target customer segments better and enhance acceptance. Furthermore, this conclusion will help to highlight existing research on the Malaysian takaful business and make practical recommendations to increase the usage of family takaful products in takaful enterprises in a similar setting.